Biocorrosion processes of offshore of oilfield equipment - Zakharova Elena; Murko Elena; Yatsevich Mariya (BIO Web of Conferences)
The issues of corrosion of offshore oilfield equipment are considered. The factors influencing the corrosion processes in the conditions of offshore fields are determined. These include-the temperature of the environment, the salt composition of sea water, the speed of currents and the presence of mechanical damage to the platform, as well as marine fouling with living organisms. The characteristics of the types of corrosion damage of marine oilfield equipment are given. The concept of biological corrosion is formulated and discussed. The reasons and consequences of the influence of this process on metal structures and non-metallic materials used for the construction of offshore platforms are highlighted. The choice of methods and methods of anticorrosive protection of offshore oil platforms requires taking into account and analyzing several parameters of the state of both the environment and the structure itself.